Combining video and GPS-tracking to study the spatial foraging distribution of a single-prey loading seabird - Ruben C. Fijn; Wouter Courtens; Bas W.R. Engels; Emiel E. van Loon; Judy Shamoun-Baranes (Avian Research)
Seabirds are valuable indicators of marine ecosystem processes and studying seabird diets can shed light on natural or human-induced variability in food-web composition. Specifically single-prey loading seabird species such as terns have the potential to act as visual sentinels of prey availability offshore. However, obtaining diet information from remote bird colonies is often challenging and time consuming. In this pilot study we present a novel approach to combine two established methods to study seabird foraging ecology, providing a powerful and cost-effective tool to study the distribution of prey items available to seabirds. We combined GPS tracking data of Sandwich Terns (Thalasseus sandvicensis) with prey-observations from a hide in 2012 and 2013, and from semi-continuously recorded camera footage in 2017. By doing so, we identified 115 approximate catch locations of prey (86 herring/sprat Clupeidae, 29 sandeel Ammodytidae). Combining GPS-data and prey observations yielded detailed knowledge on the movements and chick diets of tracked birds as well as the spatial origin and lengths of captured prey items. Further catch distances of both Clupeidae and Ammodytidae resulted in deliveries of larger prey items and thus higher energy yield per trip, but also a higher energy expenditure per trip. We discuss the limitations and potential of our methodological approach to study foraging energetics during chick-provisioning of seabirds that carry prey items visible in their beaks.